Descriptive, but not Injunctive, Normative Appeals Increase Response Rates In Web-based Surveys - Shalini Misra; Daniel Stokols; Anne Heberger Marino (Journal of MultiDisciplinary Evaluation)
Background: In an earlier experiment Misra, Stokols, & Marino (2012) found that participants who received a descriptive normative prompt in the message requesting them to complete an online survey were more likely to comply with the request compared to participants who did not receive any normative prompts.